The Implication of Studentification To Community’s Physical And Social Economicaspects In Tembalang Higher Education Area - Dewi, Santy Paulla; Ristianti, Novia Sari (Semarang State University, 2019)
Abstract. Studentification is a neighbourhood changes caused by the students’ presence in the permanent settlement then influence the area; students accomodation supply and community’s social economic aspects. This research revealed the influence of studentification in Tembalang higher education area to the physical and social economic aspects. Qualitative research method was used to explain more about the studentification influence and the Tembalang development trend. Interview conducted to some key figures in the community such as Lurah, community leaders, and students to find out their perception regarding the neighbourhood transformation. Based on analysis, it showed that studentification emerged since the Pleburan campus moved to Tembalang campus which students accomodation demand increased significantly. Moreover, the studentification influences seen from the increasing of land price, land use conversion, and students’ life style that affected the community’s job-shifting. However, the development of Tembalang higher education area still on the track based on the guidance and spatial pattern structure recommendation of Semarang Spatial Plan 2011-2030.